2019
DOI: 10.1186/s12913-019-4524-0
|View full text |Cite
|
Sign up to set email alerts
|

Waiting times for diagnosis of attention-deficit hyperactivity disorder in children and adolescents referred to Italian ADHD centers must be reduced

Abstract: Background To investigate timely access to and the time needed to complete the diagnostic path of children and adolescents with suspected attention deficit hyperactivity disorder (ADHD) in the 18 Italian Lombardy Region ADHD reference centers. Methods Data of children and adolescents enrolled in the Regional ADHD disease-oriented Registry for suspected ADHD who requested their first visit in 2013–2017 were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…The findings of the present research are in line with previous studies suggesting that externalising problems may be associated with longer waiting times than other types of problems 23 (also see a study by Smith et al 25 ) and that higher levels of severity are associated with short waiting times for ADHD diagnosis when examining only those with ADHD 22 (although in comparison with the self-management group in the present study, young people with ADHD were more likely to have longer waiting times). 22 Moreover, the findings that young people with psychosis were less likely to wait 3-4 weeks, 5-18 weeks, and ≥19 weeks, and that young people with eating disorders were less likely to wait 5-18 weeks and ≥19 weeks, are in line with recommendations for child and adolescent mental health services in England to provide treatment within 2 weeks of referral for psychosis and between 2 and 4 weeks of referral for eating disorders. 2…”
Section: Main Findings and Comparison With Findings From Other Studiessupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of the present research are in line with previous studies suggesting that externalising problems may be associated with longer waiting times than other types of problems 23 (also see a study by Smith et al 25 ) and that higher levels of severity are associated with short waiting times for ADHD diagnosis when examining only those with ADHD 22 (although in comparison with the self-management group in the present study, young people with ADHD were more likely to have longer waiting times). 22 Moreover, the findings that young people with psychosis were less likely to wait 3-4 weeks, 5-18 weeks, and ≥19 weeks, and that young people with eating disorders were less likely to wait 5-18 weeks and ≥19 weeks, are in line with recommendations for child and adolescent mental health services in England to provide treatment within 2 weeks of referral for psychosis and between 2 and 4 weeks of referral for eating disorders. 2…”
Section: Main Findings and Comparison With Findings From Other Studiessupporting
confidence: 92%
“…The pattern of findings from previous studies on the association between individual characteristics and waiting times is mixed. Some studies have found that males were more likely to have longer waiting times than females or that age was negatively associated with waiting times; [21][22][23][24] however, other studies have found that age was positively associated with waiting times. 21 Similarly, there is conflicting evidence about whether referrals from some settings such as education are associated with longer or shorter waiting times.…”
Section: Factors Linked To Waiting Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the demands of the treatment and diagnosis, the need for care and support relies on their families in many ways. Parents fill an important role in caring for their child with ADHD and in providing tasks that parents of children without such conditions are not confronted with, such as initiating and supporting professional help seeking (Sayal, 2006), coping with the complexity of ADHD-treatment, and with ADHD having a profound impact on their children's learning at school (Ghosh et al, 2016;Bonati et al, 2019). Family support is strongly linked to improved health and better psychosocial outcomes for chronically ill children, and the relationship and functioning within the family may change over time coincident with different developmental stages and levels of autonomy (Finzi-Dottan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of the literature highlighted the positive effect of psychological interventions on ADHD cognitive symptomatology and supports the inclusion of non-pharmacological interventions in conjunction with the commonly used pharmacological treatments [15]. Despite the existence of clear and specific guidelines, access to services is limited [16,17], the waiting times for diagnosis are too long [18], and the treatment outcomes depend on many factors, such as the presence of comorbidities [19]. In June 2011, an official regional registry was activated in the Lombardy Region.…”
Section: Introductionmentioning
confidence: 99%